Inserting Local Wisdom In English Material: Strategies and Benefits - Prayudha.S, Joko (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
This study aims to describe the strategies and benefits of incorporating local cultural values in English language teaching. The type of research used is library research. Data was collected through reference collection from journals, articles, or books related to local culture in teaching. The analysis shows that the use of local cultural values is able to build student awareness of culture, encourage students to love the uniqueness and value of their culture, and improve their understanding of English material. The strategies that English teachers can apply when teaching using local culture are through materials related to products or objects typical of a region, such as using pictures or photos, conducting discussions, making video projects, practicing conversations, group learning, and making podcasts. Furthermore, the benefits that occur when including local wisdom in English teaching include increasing socio-cultural awareness, making students more aware of their culture and familiar materials, developing students' character, improving students' language skills, and increasing tolerance and mutual respect. To be successful in teaching English through local culture, teachers need to design and emphasize learning materials and activities using local culture so that students are more aware of the uniqueness of their culture.